Arrival of Young Talents: The Send-down Movement and Rural Education in China - Yi Chen; Ziying Fan; Xiaomin Gu; Li-An Zhou (Global Labor Organization (GLO), 2018)
This paper studies human-capital spillovers and its persistence by exploiting a unique event in modern China|the send-down movement. From 1962 to 1979, the Chinese central government mandated the temporary resettlement of roughly 18 million urban youths to rural areas across the country. The movement's coercive features, together with strict restrictions on migration during that period, provide an ideal natural experiment to identify the causal impact of the better-educated sent-down youths (SDYs) on the less-educated local rural residents. Using a county-level dataset compiled from over 3,000 book-length local gazetteers and microlevel population censuses, we find that a greater exposure to SDYs significantly increased local residents' educational achievement. Our estimate shows that the unintended gain of rural education almost compensated the loss in urban China due to the educational disruption during the Cultural Revolution. The positive effect gradually declined as SDYs started to return to their urban homes in the late 1970s, but it never dropped to zero, indicating the persistence of human-capital spillovers. We also find suggestive evidence that the arrival of young talents reshapes the attitudes of local residents toward education.
Keywords: I25; J24; N35; O15; R23; 330; Send-down Movement; Rural Education; Human-capital Spillovers